Research Ideologies among Legal Scholars and Multidisciplinary and Interdisciplinary Academic Research Approaches - Camillus, Okuma Nwachukwu; Chibuzo, Ikenna; Ighoroje, James Ese; Cyriacus, Uwasomba Monday; Martins, Ogbonna; Okafor, Jude Chukwuemeka; Onwuta, Austin Ifeanyi; Okpara, Faith Amarachi; Chibunna, Anumege Sabastian; Emeka, Ifediba Emmanvitalis; Temuhale, Julius; Juliet, Okuma Ijeoma; et al. (Journal of Ecohumanism, 2024)
This article explores the dichotomy between traditional research methodologies and modern multidisciplinary and interdisciplinary approaches within the academic legal community in Nigeria. While disciplines such as pure science, social science, education, and arts have embraced collaborative research strategies to address complex issues, legal scholars predominantly adhere to the doctrinal style. This adherence creates a significant challenge in achieving consensus on research methodologies, data sources, and analytical techniques. The study highlights the reluctance of legal scholars and regulatory bodies like NALT to recognize the value of integrating diverse academic perspectives. By examining the current research ideologies among legal scholars, the article underscores the need for a unified approach to academic research that bridges the gap between traditional legal research and collaborative methodologies, ultimately enhancing the scope and impact of scholarly inquiry in the legal field. The research employs a qualitative design, utilizing interviews and surveys with legal students, scholars, educators, and regulatory body members to gather in-depth insights into their research practices and attitudes. Based on the findings, the article recommends promoting awareness and education on the benefits of multidisciplinary and interdisciplinary research, fostering a more inclusive research culture, encouraging regulatory bodies to endorse and support collaborative research initiatives within the legal academic community and develop a Okuma-NC (hybrid) research methodology and citation formula integrating aspects of OSCOLA, NALT, and APA, enabling seamless application in socio-legal, scientific, multidisciplinary, and interdisciplinary research within legal contexts.